The nexus between governance elements and the green economy: Evidence from Indonesian publicly listed SOEs - Nastiti Rizky Shiyammurti; Bambang Tjahjadi (Cogent Business & Management, 2023)
The author, a lecturer in Accounting at Pasim National University, completed her undergraduate studies at Telkom University Bandung (2014) and holds a Master's degree in Accounting from Unpad Bandung (2018). She is currently pursuing a Doctorate in Accounting at Airlangga University Surabaya (2023). With expertise in management accounting and financial management, she writes extensively in Sinta and Scopus-accredited journals, focusing on financial management, performance, and reporting.
Keywords: 650; audit committee; board of commissioners; green economy performance; institutional ownership; managerial ownership; State-Owned Enterprises